Three essays on development: access to services in developing countries - Mudenda, Lackson D., author; Pena, Anita Alves, advisor; Miller, Ray, advisor; Bernasek, Alexandra, committee member; Roberts, Anthony, committee member (Colorado State University. Libraries, 2023)
This dissertation aims to contribute to development economics related to sanitation and poverty in some selected developing countries using microdata. The focus is on Ethiopia, India, Peru, and Vietnam, chosen for various reasons. This culminates into three distinct essays. The first and second chapters use the Young Lives Study (YLS) data, a unique longitudinal dataset that follows a set of 12,000 children. The rationale for choosing Vietnam, India, Peru, and Ethiopia as interest countries for the YLS emerges from the desire to address child poverty effectively. This selection is guided by the substantial levels of child poverty in these regions, their cultural diversity, and the potential to generate policy-relevant recommendations. By considering these factors, the YLS ensures a comprehensive examination of child poverty within diverse contexts and in line with the tracking of progress towards the United Nations Millennium Development Goals (MDGs), paving the way for evidence-based policy recommendations to improve the lives of children in these countries (Barnett et al., 2013). The final chapter uses the World Bank's Living standard measurement survey, the Ethiopian Socioeconomic Survey (ESS). The first chapter of this dissertation uses the unique longitudinal data from four low- and middle-income countries to examine the relationship between early-life access to sanitation services and children's cognitive development. The primary focus of this chapter is directed towards the younger cohort rather than the older cohort of the YLS, as it is exclusively within the younger cohort that we can ascertain early exposure to sanitation practices occurring between the age range of 6 to 18 months. Conversely, the youngest child within the older cohort is approximately 5 years old, rendering it insufficient for observing the said early access to sanitation. Therefore, chapter one tracks 8,062 children over 15 years and uses a fixed effects model to analyze the impact of early access to flush toilets and pit latrines on their vocabulary, math scores and health indicators, including height-for-age and BMI-for-age z-scores. The study also uses the hierarchical linear models (HLMs) to investigate the presence of community spillovers. The treatment variable in this chapter is early life access to sanitation both at the household and the community levels. The findings suggest a significant positive correlation between early access to sanitation services and children's cognitive development, although the results vary across countries. The study also supports a health mechanism: early access to flush toilets is significantly associated with improved height-for-age and BMI-for-age z-scores. Additionally, the study finds evidence of community spillovers for vocabulary but not math. The second chapter examines the relationship between access to private sanitation facilities at home and psychosocial development among adolescents aged 12-22 in India and Ethiopia. In this study, the focus is on both the younger and older cohorts limited to rounds 4 and 5 of the YLS as they specifically encompass the adolescent phase and when extensive psychosocial outcomes were collected for both cohorts. Psychosocial outcomes were also collected using a smaller and modified set of statements in round 3, but in round 4, they were expanded and updated to better reflect validated scales and cater to older children (Ogando and Yorke, 2018). The treatment variable in this chapter is private sanitation in the household. Using a longitudinal two-way fixed effects model, the study finds that access to private sanitation (flush toilets or pit latrines in the household) is associated with significantly higher self-efficacy and self-esteem for adolescent girls but not boys. Associations are stronger for girls who live in communities with higher overall access to private sanitation, suggesting relative access may matter more for psychosocial development than absolute access. There is also evidence of a significant correlation with improved peer relations for girls in early (age 12 to 15) but not late (age 19 to 22) adolescence. The results do not portray evidence that the findings are operating through improved physical health, suggesting there may be a direct impact of private sanitation facilities at home and psychosocial development in adolescent girls. These findings suggest interventions should consider the health benefits of hygienic waste management, the potential gains from improved sanitation experiences for women and girls, and the potential unintended spillover effects of inequitable roll-out. Ethiopia is one country that has been unfortunate enough to experience severe drought in the last few decades. This has affected life in Ethiopia at so many levels. Specifically, the challenges of access to clean drinking water and cooking fuels have disproportionately impacted females as they spend more time collecting these resources. This has had the negative consequence of perpetuating time poverty among this group of people, and thereby their inability to participate in the labor market for paid work fully. Following an unbalanced panel of households from the World Bank's living standards measurement survey, this chapter uses the Ethiopian Socioeconomic Surveys (ESS) between 2012 and 2016 to investigate the determinants of households' choice of cooking fuel and drinking water sources in rural and small towns of Ethiopia. The final chapter investigates the factors influencing households' decisions regarding choices of cooking fuel and drinking water sources in rural and small towns of Ethiopia. The study employs probit models (ordered and regular) to examine the effects of improved fuel and water sources on labor outcomes by leveraging variations in access. The findings are that household size, asset ownership, and the education level of the household head as well as their ages, are key determinants influencing the choice of cooking fuel and drinking water. Furthermore, adopting improved water sources significantly and positively impacts family business labor, while using improved cooking fuels significantly enhances agricultural labor. These findings demonstrate the potential benefits of transitioning to improved fuel and water sources in rural Ethiopia, emphasizing the importance of considering social and economic factors in sustainable development initiatives.